Incidencia de la educación sexual en el desarrollo psicosocial en los estudiantes de 5to grado de educación básica en la Unidad Educativa Particular Padre Marcos Benetazzo ubicada en el cantón Babahoyo - Muñoz Carrasco, Marilyn Dayanna (2019)
The purpose of this research is to give way to promote sexual education, being a problem in students who go through this stage of their lives. To contribute to education in a change of skills and attitudes in students to promote and prevent sexually transmitted diseases and unwanted pregnancies in them, currently one of the main problems that afflict children and young students who begin their lives , is the unwanted pregnancy, this leads to non-assertive consequences to successfully complete their studies being a factor for abandonment, not in all cases, as some students have the support of their parents, but sadly this problem has gone increasing in our times thanks to the poor and scant information that reaches students about issues of sexuality in schools, in a way the late and not generalized information to all educational institutions cause this problem to increase, due to the above statistics show that unwanted pregnancy among students continues to increase.